2022
DOI: 10.3390/ma15051774
|View full text |Cite
|
Sign up to set email alerts
|

Bitumen Binders Modified with Sulfur/Organic Copolymers

Abstract: With the continuing growth of waste sulfur production from the petroleum industry processes, its utilization for the production of useful, low-cost, and environmentally beneficial materials is of primary interest. Elemental sulfur has a significant and established history in the modification of bitumen binders, while the sulfur-containing high-molecular compounds are limited in this field. Herein, we report a novel possibility to utilize the sulfur/organic copolymers obtained via the inverse vulcanization proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Following the polymer addition, the mixture was mechanically agitated using an IKA RW 20 mixer for 60 min at 1500 rpm to make the blend essentially homogeneous. Subsequently, the PMA was prepared by mixing it with a calculated sulfur content, including ratios of 0.075%, 0.03%, 0.1%, 0.3%, and 0.5% by weight of binder [9,16,24,26,40,41]. These specific ratios were chosen based on pre-screening tests, which indicated their suitability for the study, and the selection aligns with findings from relevant research.…”
Section: Methodsmentioning
confidence: 99%
“…Following the polymer addition, the mixture was mechanically agitated using an IKA RW 20 mixer for 60 min at 1500 rpm to make the blend essentially homogeneous. Subsequently, the PMA was prepared by mixing it with a calculated sulfur content, including ratios of 0.075%, 0.03%, 0.1%, 0.3%, and 0.5% by weight of binder [9,16,24,26,40,41]. These specific ratios were chosen based on pre-screening tests, which indicated their suitability for the study, and the selection aligns with findings from relevant research.…”
Section: Methodsmentioning
confidence: 99%
“…An effective way to solve this problem is to improve the structure and properties of bitumen by using inexpensive modifiers of various types. [1][2][3][4] The processes of modification of oil residues are divided into physical and chemical. Physical modification of oil residues involves the introduction of various types of applications into their composition, which ensure improvement of operational characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Coal tar pitch has been widely explored and employed as a bitumen modifier due to their various functional groups. Low-molecular organic molecules (formaldehyde and maleic anhydride) [17] [18] and sulfur/organic copolymers [19] are generated as byproducts of coal conversion. G. Strap et al [20], and M. Çubuk, et al [21] found out that phenol-formaldehyde resins can be fairly effective petroleum bitumen modifiers.…”
Section: Introductionmentioning
confidence: 99%